2008
DOI: 10.1007/s10661-008-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of rapid bioassessment approaches using benthic macroinvertebrates for Thai streams

Abstract: Thailand currently lacks formal bioassessment approaches and protocols to assist management decisions for water quality. The aim of this research is to develop a practical method of rapid bioassessment for a professional level by using benthic macroinvertebrate assemblages for streams in Thailand. Eleven reference and nine test sites were sampled in the headwater streams of the Loei River and adjacent areas to explore the development of a practical protocol. Specific physico-chemical parameters were selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…Using family level identification is recommended in case of incomplete taxonomic knowledge (Thorne & Williams, 1997) and is qualified as sufficient to assess environmental disturbance (e.g. in Thailand; Boonsoong et al, 2008). Recent studies conducted in tropical areas showed that family-level resolution successfully detect anthropogenic impairment (Dedieu et al, 2015).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using family level identification is recommended in case of incomplete taxonomic knowledge (Thorne & Williams, 1997) and is qualified as sufficient to assess environmental disturbance (e.g. in Thailand; Boonsoong et al, 2008). Recent studies conducted in tropical areas showed that family-level resolution successfully detect anthropogenic impairment (Dedieu et al, 2015).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…In 2009, the Mekong River Commission (MRC) estimated that the majority of the projects in the Lower Mekong Basin were located in Lao PDR (MRC, 2010). Interest in using macroinvertebrates to assess environmental changes is growing in the region such as in Vietnam (Hoang & Bae, 2006;Jung et al, 2008;Hoang et al, 2010) and in Thailand (Mustow, 2002;Getwongsa & Sangpradub, 2008;Thani & Phalaraksh, 2008;Boonsoong et al, 2008). However, in Lao PDR, knowledge and use of benthic macroinvertebrates for bioassessment studies remain scarce (Davidson et al, 2006;Pathoumthong & Vongsombath, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since the effectiveness of biomonitoring protocols depends mainly on the time required and on the overall costs, techniques that optimize the cost-benefit have been developed Pinna et al, 2013Pinna et al, , 2014. Nevertheless, caution is needed since the technique and the way in which samples are collected and processed may influence the description of the studied community (Boonsoong et al, 2009;Di Sabatino et al, 2014). In fact, reducing effort and costs is not the only aim of subsampling methods, but also of paramount concern is the need to gain information not substantially biased by the procedure and capable of answering research questions (Barbour and Gerritsen 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The Office of Environmental Policy and Planning (OEPP) in Thailand identified the importance of wetlands based on the criteria of the Convention on Wetlands (Ramsar Convention) at 3 levels: international, national and local (OEPP, 2002). The current water quality assessment tools based on macroinvertebrate parameters, which have been extensively reviewed in the literature, are already in use to assess the ecological quality of streams and rivers in Thailand (Thorne and Williams, 1997;Mustow, 2002;Boonsoong et al, 2009;Getwongsa et al, 2010, Uttaruk et al, 2011), yet there are currently no working macroinvertebrate assessment systems for wetlands; indeed, the few studies addressing wetland monitoring have focused only on fish and birds (OEPP, 2002;Pagdee et al, 2007). Accordingly, the aim of this study was to develop a biotic index using benthic macroinvertebrates as a bioassessment tool for wetlands.…”
Section: Introductionmentioning
confidence: 99%